2020
DOI: 10.2147/ijn.s247935
|View full text |Cite
|
Sign up to set email alerts
|

<p>Primary Studies on Construction and Evaluation of Ion-Sensitive in situ Gel Loaded with Paeonol-Solid Lipid Nanoparticles for Intranasal Drug Delivery</p>

Abstract: Background: Paeonol (PAE) is a potential central neuroprotective agent with poor water solubility and rapid metabolism in vivo. The key to improve the clinical application of PAE in the treatment of neurodegenerative diseases is to improve the brain delivery of it. The purpose of this study was to construct a paeonol-solid lipid nanoparticles-in situ gel (PAE-SLNs-ISG) drug delivery system based on nose-brain transport pathway. Materials and Methods: In this study, the stability of PAE in simulated biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The olfactory pathway has been indicated in some studies. For example, fluorescence response to IN administered Cyanine7 NHS ester-loaded SLNs (Cys7-SLNs) was clearly observed in olfactory bulb, cerebellum, and striatum [ 12 ]. Furthermore, a proportion of drugs entering the respiratory region can be transported directly to the brain through the trigeminal nerve pathway via extraneuronal or intraneuronal routes although this pathway is less important than the olfactory pathway [ 7 ].…”
Section: Nose-to-brain Delivery Pathways and Feasibilities Of Slns An...mentioning
confidence: 99%
See 2 more Smart Citations
“…The olfactory pathway has been indicated in some studies. For example, fluorescence response to IN administered Cyanine7 NHS ester-loaded SLNs (Cys7-SLNs) was clearly observed in olfactory bulb, cerebellum, and striatum [ 12 ]. Furthermore, a proportion of drugs entering the respiratory region can be transported directly to the brain through the trigeminal nerve pathway via extraneuronal or intraneuronal routes although this pathway is less important than the olfactory pathway [ 7 ].…”
Section: Nose-to-brain Delivery Pathways and Feasibilities Of Slns An...mentioning
confidence: 99%
“…Sun et al developed a paeonol-loaded SLN gel (0.4% deacetylated gellan gum and 0.3% HPMC) [ 12 ]. The authors found that brain accumulation was better for a cyanine7 NHS ester-loaded SLN gel (IN) than cyanine7 NHS ester-loaded SLNs (IV).…”
Section: In Vivo Evaluations Of Sln and Nlc-based Formulations For No...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [ 80 ] evaluated the in vitro cytotoxicity in RPMI 2650 cells of an in situ gel containing paeonol-loaded SLN, paeonol-loaded SLN, blank SLN and a blank in situ gel, using the MTT method. The cell viability of all tested formulations, in the concentration range of 0.001–10 µg/mL, was higher than 90%, indicating biocompatibility.…”
Section: Solid Lipid Nanoparticles (Sln) and Nanostructured Lipid Carriers (Nlc) For Nasal Deliverymentioning
confidence: 99%
“…Therefore, there were attempts to design intranasal systems aiming to increase drug concentration in the brain structures via the prolonged exposure of nasal mucosa to the drug carrier. The formulation including solid lipid nanoparticles with paeonol suspended in 0.4% deacetylated GG as an in situ gelling agent, was employed to alleviate the first-pass effect and to enable brain delivery via the olfactory nerve pathway [ 15 ]. Resveratrol loaded nanosuspension, based on 0.6% ( w/v ) deacetylated GG, was employed to exploit an analogous delivery route.…”
Section: Non-selective Ion-sensitive Formulationsmentioning
confidence: 99%